Genotypic diversity of Coffea canephora cv. Conilon identified through leaf morpho- and eco-physiological traits - dos Santos, Millena Monteiro (2024)
The authors would like to thank Universidade Federal do Espírito Santo (UFES) , Fundação de Amparo à Pesquisa e Inovação do Espírito Santo (FAPES - 2022-WTZQP) , and the Conselho Nacional de Desenvolvimento Científico e Tecnológico ( CNPq - 309535/2021-2 ). Publisher Copyright: © 2023